Bridging the gap between high temperature and low temperature oxidation of 316 L. (October 2020) - Wonneberger, Robert; Lippmann, Stephanie; Abendroth, Barbara; Carlsson, Anna; Seyring, Martin; Rettenmayr, Markus; Undisz, Andreas
Abstract: The formation of multilayered oxides on 316 L is reassessed, considering the recently discovered phenomenon of steep concentration gradients in single corundum-type oxide grains after high temperature oxidation. Evidence is shown that the phenomenon applies to oxidation at high and low temperature, with a three-layered Cr-Fe-Cr oxide being preceded by a two-layered Cr-Fe oxide that directly links to observations reported for the native oxide. A coherent growth mechanism is proposed, with the reaction front shifting position depending on the annealing temperature. The absence of spinel-type oxides is discussed considering the Mn distribution.